Formulation and Evaluation of Liquid Soap Containing Ethanolic Extract of Eleutherine palmifolia (L.) Merr. Leaves - Erna Prihandiwati; Nur Ainah; Muhammad Ma'ruf; Senya Puteri Amalia; Eka Kumalasari; Muhammad Aulia Irwansyah; Olivia Olivia (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2026)
Eleutherine palmifolia (L.) Merr is a native plant of South Kalimantan with considerable potential for health applications. Previous studies have reported that its leaves contain various bioactive compounds, including alkaloids, flavonoids, steroids, tannins, and saponins, which contribute to antibacterial and antioxidant activities. Liquid soap is one of the most practical and widely used dosage forms for antibacterial purposes. Therefore, this study aimed to formulate and evaluate the physical characteristics of liquid soap containing ethanol extract of E. palmifolia leaves and to determine the optimal formulation that meets quality standards. An experimental study was conducted using three formulations with different concentrations of Cocamide DEA (0.5%, 1%, and 1.5%). The formulations consisted of E. palmifolia leaf extract, virgin coconut oil (VCO), potassium hydroxide (KOH), Na-CMC, stearic acid, BHT, lemongrass oil, and distilled water. The prepared liquid soaps were evaluated for pH, viscosity, foam stability, storage stability, hedonic properties, antibacterial activity, and irritation potential. The results showed that Formula 2 containing 1% Cocamide DEA exhibited the most favorable overall characteristics, providing a balance between physical stability, user comfort, and respondent acceptance. Formula 3 produced the highest foam stability but caused a dry sensation on the skin. Furthermore, Formula 2 containing 1.5% E. palmifolia extract demonstrated strong inhibitory activity against Staphylococcus aureus and moderate inhibitory activity against Escherichia coli. All formulations met the required quality parameters and showed no irritation effects. In conclusion, liquid soap formulated with 1% Cocamide DEA and 1.5% E. palmifolia leaf extract was identified as the optimal formulation. The conclusion of the results of this product meets the requirements of SNI 06-4085-1996, exhibited good physical stability, was non-irritating, and showed potential as a natural antiseptic liquid soap.